PENGARUH MODEL SAVI TERHADAP KETERAMPILAN PROSES SAINS DAN PENGUASAAN KONSEP PADA PEMBELAJARAN IPA - Khaidir Fadil; Amran Amran (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
Abstract.The aim of this study  is to portray the effect of SAVI Model towards students' science process skills and students' conceptual mastery on the subject material about Energy. The study was done under the quantitative paradigm with quasi experiment approach by utilizing the purposive sampling. The population of the study was 149 4th grader students with 37 students from 4D as the experimental class where the SAVI Model was applied and 38 students from 4A as the control class where the classical instructions was conducted. The data was gathered through test and observation sheet. The data was analyzed by utilizing the SPSS version 23 through  test-1. The result indicates that there's a significant effect of SAVI Model toward students' science process skills and their conceptual mastery on the subject material about Energy at MIN 2 Bogor by showing the average mark of 79,52 on students conceptual mastery and 89,98 on students' science process skills.Keywords: SAVI model; mastery of concepts; science process skills;